ELECTRONIC SPACES AS AN ALTERNATIVE TO TRADITIONAL CLASSROOM DISCUSSION AND WRITING IN SECONDARY ENGLISH CLASSROOMS - Lee, Sangmin (Online Learning, 2005)
In most secondary school classrooms, teachers are still authoritative, central-figures. They talk and teach while students listen and passively receive what the teacher says. Regarding writing, the situation is similar. Students write only to the teacher, the person who grades their papers. In this environment, classroom dynamics are monologic and learning is limited to individuals. To establish a more constructivist learning environment, this study explored electronic spaces as alternatives to classroom dialogue and writing. This paper observed two 10th grade English classrooms (51 students) who participated in an exploration of Lord of the Flies using an electronic discussion board through which they collaboratively constructed knowledge. In short, the discussion board facilitated both student-centered dialogues and an authentic writing environment, which promoted a dynamic learning community and healthy writer’s identity for the students. Three salient features of the discussion board activity will be explored to support this claim: a) the students’ use of questions and hypothetical/conditional sentences, b) the students’ interaction patterns, and c) the dialogic/progressive patterns of co-construction of knowledge on the discussion board.